2019
DOI: 10.3897/zookeys.841.33271
|View full text |Cite
|
Sign up to set email alerts
|

The study of hidden habitats sheds light on poorly known taxa: spiders of the Mesovoid Shallow Substratum

Abstract: The scarce and biased knowledge about the diversity and distribution of Araneae species in the Iberian Peninsula is accentuated in poorly known habitats such as the Mesovoid Shallow Substratum (MSS). The aim of this study was to characterize the spiders inventory of the colluvial MSS of the Sierra de Guadarrama National Park, and to assess the importance of this habitat for the conservation of the taxon. Thirty-three localities were selected across the high peaks of the Guadarrama mountain range and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…included species that we had overlooked in the previous version of the checklist-see, e.g., missing species pointed out in ref. 33 ; and III). updated taxonomy following recent nomenclatural changes 34 and corrected a few mistakes we detected.…”
Section: Background and Summarymentioning
confidence: 92%
“…included species that we had overlooked in the previous version of the checklist-see, e.g., missing species pointed out in ref. 33 ; and III). updated taxonomy following recent nomenclatural changes 34 and corrected a few mistakes we detected.…”
Section: Background and Summarymentioning
confidence: 92%
“…This population in Galicia increases the number of Spanish regions where S. iberica has been found to five, after being recorded in Andalusia, the Valencian Community, Cantabria (all: Bosmans et al 2010) and possibly Castile and León (identified as Sintula cf. iberica in Ledesma et al 2019).…”
Section: Sintula Iberica Bosmans 2010mentioning
confidence: 99%
“…In fact, being active hunters rather than web-builders, Dysderidae are frequently associated with MSS habitats , and different species have been collected in MSS in other areas [e.g. Dysdera (Arnedo et al, 2007;Pipan et al, 2010), Harpactocrates and Harpactea (Ledesma et al, 2019)].…”
Section: Ecological Drivers Of Species Distributionsmentioning
confidence: 99%